Spatial Politics: The Polemic on the Implementation of Permanent Bike Lanes on Jalan Sudirman-Thamrin DKI Jakarta - Diah Ayu Rachma; Luthfi Abduh Alhakim (PERSPEKTIF, 2023)
The purpose of this study was to find out the politics of spatial planning in terms of the polemic on the implementation of permanent bicycle lanes on Jalan Sudirman-Thamrin DKI Jakarta. Problems with the characteristics of the rules regarding special bicycle lanes on Jalan Sudirma-Thamrin which are not accompanied by careful consideration. Instead of overcoming the chaos, traffic jams are getting worse when the bike lanes are empty. To approach this problem using Levebre's spatial reference theory. The method used in data analysis is qualitative analysis, which describes quality data in sentences that are orderly, coherent, logical, non-overlapping, and effective. The technique used in collecting research materials is library research, which includes collecting, reading, and tracing various journals, books, laws and regulations, scientific papers, literature from the internet, and other materials. All of this data is then analyzed from a political perspective where this analysis is viewed from a political perspective. The results of the study show that the background of bicycle lanes is to equate bicycle lanes with motorized vehicle lanes to improve the safety of cyclists. The polemic that occurs with regard to Levebre's 3 theories is that bicycle lanes actually cause traffic jams instead of reducing congestion and are considered a failure even though special bicycle lanes are a division of space that unites bicycle, motorbike and car lanes. From a political point of view, there are still a lot of criticisms for the special lane for bicycles, which was originally used as a political vehicle for the government, but it did not work as it should, causing a lot of criticism.